Experimental investigation of near-critical CO2 heat transfer performance in a closed natural circulation loop. (1st November 2022) - Li, Yuanlu; Yuan, Baoqiang; Du, Wenjing
Highlights: A closed natural circulation loop experimental system of CO2 was established. Heat transfer of near-critical pressure and filling ratio in the closed loop was studied. Heat transfer deterioration was observed at supercritical pressure. The transition of near-critical heat transfer mechanism was analyzed. Abstract: The natural circulation system based on supercritical CO2 has attracted attention due to its simple structure and safety compared with the forced circulation system. This work presented an experimental investigation of the heat transfer characteristics of CO2 based on natural circulation. A closed loop natural circulation experimental system was built, which was specially designed for near-critical pressure experiments. The effects of filling ratio, coolant temperature, heat transfer rate and system pressure were carefully discussed. Experimental results illustrated the loop had excellent heat transfer capability at subcritical pressure, but the heating section showed heat transfer deterioration at supercritical pressures. The heat transfer behaviors were analyzed. From subcritical pressure to supercritical pressure in the loop, the heat transfer mechanism transforms from two-phase transition to supercritical single-phase convection. Gas-like layer and insulating layer will form near the wall in the heating section, resulting in a large thermal resistance at the wall for heat to enter the core flow.